Treatment of depression and poor quality of life through breathing training in hemodialysis patients - Hayfa Almutary; Noof AlShammari (BMC Nephrology)
Abstract Background The management of depression in patients undergoing hemodialysis remains challenging and affects quality of life; however, there is a possibility that breathing exercises may be effective in this context. Thus, the purpose of this study was to evaluate the effectiveness of a breathing training program on quality of life and depression among patients on hemodialysis. Methods A one-group pretest-posttest quasi-experimental design was used. Data were collected from hemodialysis patients at three dialysis centers. Initial baseline data were collected, and a breathing training program was implemented. The program included three types of breathing exercises. A total of 41 participants completed the study. The participants were asked to perform the breathing training program three times a day for 30 days. The impact of the intervention on patients’ quality of life and depression was measured using both the Kidney Disease Quality of Life Short Version and the Beck Depression Inventory-Second Edition. Results A significant decrease in the overall depression score was observed after implementing the breathing training program (BDI-II mean difference =-3.9, 95% CI:0.35–7.45, p = 0.03). The intervention has also had significant improvements on overall quality of life (KDQOL mean difference = 6.09, 95% CI: 0.48–11.70, p = 0.03) and a reduction in the symptoms and problems domain (domain mean difference = 6.71, 95% CI: 0.01–13.40, p = 0.05). There were some improvements on other quality of life domains but did not reach the statistical differences after program implementation. Conclusions Breathing exercises are associated with improved quality of life and reduced depression among HD patients, providing a simple and cost-effective intervention.